Assessing the relevance of the entrepreneurship module in general studies courses to music students in Obafemi Awolowo University, Osun state, Nigeria (2021)
The increasing rate of unemployment is a major concern in many growing economies in Africa, including Nigeria. As a pragmatic response to the unpleasant Situation, the Nigerian government introduced entrepreneurial education in institutions of higher learning, designed to equip students with essential skills needed to be job creators-entrepreneurs, rather than job seekers after graduation. These entrepreneurship courses are generally taught to students across disciplines under the General Studies (GST) Programme of different institutions. The question, then, is: can these entrepreneurial courses adequately prepare music students for entrepreneurship in the music industry? The article, therefore, assesses the relevance of entrepreneurial course(s) taught by the GST Programme to music students. It discusses the students' understanding of entrepreneurship within the context of musical arts. The study employed a survey research design with the use of structured questionnaires. Sixty undergraduate students (male, N=32, female, N= 28) of the Department of Music, Obafemi Awolowo University (OAU), who offered GST entrepreneurship courses in the university, were randomly selected from 100 to 400 levels. Results showed a mixed Position; one on hand, the larger percentage of the students agreed that the concept of entrepreneurship taught in GST curriculum is very relevant to music. On the other hand, most students agreed that GST entrepreneurship courses are not sufficient in preparing them for music entrepreneurship. This article argues that entrepreneurship taught out of the context of music to music students may be counterproductive. Therefore, the study öfters some recommendations and further challenges music educators and scholars alike in rethinking music entrepreneurship education as essential 'add-ons' to the scholarship and practice of music for human capacity development in Nigeria